Sin criterios Kant, Whitehead, Deleuze y la Estética. Traducción de Román Suárez y Laureano Ralón. - Shaviro, Steven (Open Humanities Press, 2020)
In Without Criteria, Steven Shaviro proposes us to explore a philosophical fantasy: to imagine a world in which Alfred North Whitehead takes the place of Martin Heidegger. What if Whitehead, instead of Heidegger, had set the agenda for postmodern thought? While Heidegger asks: "Why is there something and not rather nothing?", Whitehead asks: "How is it that there is always something new?" Shaviro argues that, in a world where virtually everything - from popular music to DNA - is being sampled and recombined, Whitehead's question is arguably the most pressing.